2022
DOI: 10.3390/genes13122214
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis-Related lncRNA Gene Signature Establishes a Prognostic Model of Gastric Adenocarcinoma and Evaluate the Effect of Antineoplastic Drugs

Abstract: Background: One of the most frequent malignancies of the digestive system is stomach adenocarcinoma (STAD). Recent research has demonstrated how cuproptosis (copper-dependent cell death) differs from other cell death mechanisms that were previously understood. Cuproptosis regulation in tumor cells could be a brand-new treatment strategy. Our goal was to create a cuproptosis-related lncRNA signature. Additionally, in order to evaluate the possible immunotherapeutic advantages and drug sensitivity, we attempted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…AL590705.3 has been confirmed to serve as a prognostic predictor in multiple tumor types, including gastric cancer and HCC. [35,36] Previous bioinformatics analysis have also demonstrated the potential of AL590705.3 as a prognostic biomarker or therapeutic target. [37,38] Previous studies [39][40][41][42] have used AC026412.3 in the development of multiple prognostic models of HCC with satisfactory performance.…”
Section: Discussionmentioning
confidence: 99%
“…AL590705.3 has been confirmed to serve as a prognostic predictor in multiple tumor types, including gastric cancer and HCC. [35,36] Previous bioinformatics analysis have also demonstrated the potential of AL590705.3 as a prognostic biomarker or therapeutic target. [37,38] Previous studies [39][40][41][42] have used AC026412.3 in the development of multiple prognostic models of HCC with satisfactory performance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cuproptosis is closely related to the prognosis of pan-cancers, activation/inhibition of cancer signature pathways, and regulation of the tumor microenvironment ( 51 ). Moreover, the prognostic risk model established by cuproptosis-related lncRNAs has been shown in gastric adenocarcinoma ( 52 ), hepatocellular carcinoma ( 53 ), non-small cell lung cancer ( 54 ), and colorectal cancer ( 55 ), all of which provide a certain basis for individual prognosis and drug efficacy. Similarly, risk models constructed by cuproptosis-related miRNA also play a role in the prediction and treatment of hepatocellular carcinoma ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent research had also identified cuproptosis, a copper-dependent regulated cell death mechanism, as a potentially new treatment strategy for cancer. A lncRNA signature linked to cuproptosis was found to be associated with prognostic predictors for stomach adenocarcinoma (STAD), indicating its potential as a biomarker for risk stratification, evaluation of possible immunotherapy, and assessment of treatment sensitivity for STAD ( 25 , 26 ). Although thyroid hormones played an important role in the processes related to cancer occurrence and progression, their mechanisms were complex and multifaceted.…”
Section: Discussionmentioning
confidence: 99%